The right of foreigners to purchase agricultural lands in Romania: Cross-border conflict mediation - Ioan Niculae Alecu; Felix-Dimitrie Ciocan; Adriana Badea; Gabriela Gyongy Mihuţ (Agrarian Economy and Rural Development - Realities and Perspectives for Romania. 5th Edition of the International Symposium, November 2014, Bucharest, 2014)
Ever since becoming a member state of the European Union, Romania had to adapt its internal laws so that the citizens of other EU member states, or those of other entities for which this right is acknowledged by Law 17/2014, stateless persons residing in these states and legal persons established in accordance with the internal laws of these states can benefit from a regulatory framework in virtue of which they can acquire the right of private property over Romanian agricultural fields, under the same conditions as Romanian citizens, stateless persons based in Romania or Romanian legal persons. Outsourcing the civil circuit over the Romanian agricultural fields raises a serious question over the reaction of the society, which is still vibrant to anything that concerns the preservation of property over the ancestral land.
Keywords: 330; foreigners; mediation; conflict; land; alienation